Mechanisms through which exercise reduces symptom severity and/or functional impairment in posttraumatic stress disorder (PTSD): Protocol for a living systematic review of human and non-human studies [version 3; peer review: 2 approved, 1 not approved] - Fiona J. Ramage; Edoardo G. Ostinelli; Claire Stainsfield; Spyridon Siafis; Virginia Chiocchia; Simonne Wright; Francesca Tinsdeall; Claire Friedrich; James Thomas; Malcolm Macleod; Toshi A. Furukawa; Georgia Salanti; et al. (Wellcome Open Research)
Background Exercise can play an important role in reducing symptom severity and improving functional impairment in patients with posttraumatic stress disorder (PTSD). However, the precise mechanisms underpinning the effect of exercise in PTSD management are not fully understood. This living systematic review aims to synthesize and triangulate the evidence from non-human and human studies to gain insight into the biopsychosocial mechanisms through which exercise reduces symptom severity and functional impairment. Methods Independent searches will be conducted in electronic databases to identify eligible studies. Two reviewers will independently conduct the study selection, data extraction, and risk of bias assessment. We will extract outcome data and variables that can act as effect modifiers or as mediators of the effect of exercise. For the non-human studies, outcome data will include the non-human equivalents of PTSD symptom clusters. For human studies, the primary outcome will be PTSD symptom severity. The secondary outcomes will be avoidance symptom severity, reexperiencing symptom severity, hyperarousal symptom severity, negative cognitions and mood severity, functional impairment, loss of PTSD diagnosis, and dropout rates. To explain the biopsychosocial mechanisms through which exercise affects the outcome of interest, we will extract effects that relate to the impact of exercise on potential mediating variables and the effect of the later outcomes. Comparison of within-study direct and indirect effects obtained from mediation analysis, when reported, will provide insight into the importance of the examined mediator. If appropriate, we will synthesize study results using meta-analyses. We will examine potential effect modifiers of the total exercise effect to understand better the impact of exercise on PTSD symptoms and function impairment (when possible). The evidence about the potential mediators of the association between exercise and PTSD-related outcomes will be considered in a consensus meeting when sufficient evidence is available. Protocol registration PROSPERO-ID: 453615